Toward characterization and definition of fibromyalgia severity - Silverman, Stuart (BioMed Central, 2010)
BACKGROUND: There are no standard criteria for defining or assessing severity of fibromyalgia (FM) as a condition as fibromyalgia is associated with multiple symptom domains. The objective of this study was to evaluate whether patient self-reported severity of FM is associated with severity of pain and sleep interference and the presence of core co-morbidities. METHODS: We recruited individuals ≥ 18 years of age with a clinician-confirmed diagnosis of FM ≥ 3 months and a current pain rating >2 on a 0-10 numeric rating scale (NRS). Patients completed a questionnaire by mail in which they self-rated their FM severity (very mild, mild, moderate, and severe), their current pain severity and extent of sleep interference (NRS; mild, 0-3; moderate, 4-6, severe, 7-10), and provided information (yes/no) on the presence of core comorbidities (symptoms of depression, anxiety, sleep problems, back pain, neck pain) and medication use for FM. The core symptoms of FM were stratified to assist with patient characterization. Analysis of variance (ANOVA) was used to explore the relationship between self-reported FM severity and continuous variables (pain severity and sleep interference), and Mantel-Haenszel chi-square analysis was used to evaluate the trend in the proportions of patients reporting use of medications and core symptoms of FM by severity of FM. To complement patient-reported FM severity and to understand physicians' perspectives, a survey was performed among 28 physician specialists (rheumatology, neurology, anesthesiology/pain management, family practice, internal medicine, and psychiatry) to determine what they assessed when evaluating FM severity in clinical practice. RESULTS: The population (N = 129) of FM patients was predominantly female (89.1%), with a mean age of 49.4 ± 11.0 years, and 81.4% reported duration ≥ 2 years. Self-reported FM severity was moderate/severe in 86.0% of patients; mean current pain score was 6.40 ± 2.19 (moderate), and mean sleep interference score was 7.28 ± 2.23 (severe). Greater FM severity was significantly associated with higher levels of current pain and sleep interference (p < 0.0001), the proportion of patients reporting FM medication use (p = 0.0001), and the presence of core comorbidities (p < 0.05). Pain, functional disability, and fatigue severity were ranked as the top three criteria by the highest proportion of physicians when evaluating FM severity. CONCLUSION: With higher self-reported FM severity, patients have greater pain and sleep interference as well as increased frequency of core comorbidities. Further investigation into understanding FM severity is warranted.